Struktur, Perilaku dan Kinerja Pasar Beras di Kabupaten Sambas - Sari, Dian; Wilujeng, Wilis Widi; Novita, Uray Dian (Universitas Galuh, 2025)
The purpose of this study was to identify marketing channels, analyze the structure, behavior and market performance of each rice marketing channel in Sambas Regency. This research was conducted in Sambas Regency which was purposively determined with the consideration that Sambas Regency is the largest rice producer in West Kalimantan. The research was conducted in Sambas Regency. Farmer respondents used were 50 farmers, Determination of the sample of traders and marketing institutions involved was done by snowball sampling method by following the flow of information from respondent farmers. Data analysis used in this study was quantitative descriptive analysis. The results of the research show that the market structure at the farm level tends to approach a perfectly competitive market structure. The market structure at the milling level tends towards oligopsony. Large traders tend to be oligopsony towards farmers. The market structure at the retailer level tends to approach a perfectly competitive market for farmers. Rice market behavior can be seen in the sales and purchase activities where traders negotiate with farmers. The payment system is generally done in cash and a small portion in advance. Cooperative Relationships Successful wholesalers build long-term relationships with farmers in their region. By maintaining good relationships, collectors can get priority when farmers want to sell their crops. Market performance analysis shows that marketing channel I is the most efficient channel because it has no margin and a relatively large farmer's share.